Proposal for a revised Barthel index classification based on mortality risk assessment in functional dependence for basic activities of daily living - Martín Moreno, Vicente; Martínez Sanz, María Inmaculada; Martín Fernández, Amanda; Guerra Maroto, Sara; Sevillano Fuentes, Eva; Pérez Rico, Elena; Sánchez González, Irene; Fernández Gallardo, Miriam; Herranz Hernando, Julia; Benítez Calderón, María Palma; Calderón Jiménez, Laura; Sánchez Rodríguez, Elena; et al. (Frontiers in Public Health, 2025)
IntroductionFunctional dependence on the performance of basic activities of daily living (ADLs) is associated with increased mortality. In this study, the Barthel index and its activities discriminate long-term mortality risk, and whether changes in this index are necessary to adapt it to detect mortality risk is examined.MethodsLongitudinal study, carried out at the Orcasitas Health Center, Madrid (Spain), on the functional dependent population (Barthel ≤ 60). It included 127 people, with a mean age of 86 years (78.7% women and 21.3% men). Functional capacity was assessed using the Barthel index, and this index and each item it contains were analyzed as a test in relation to survival at three years, using tools that evaluate precision, discrimination, and calibration. The date of death was obtained from the health system.ResultsGreater dependency to perform chair-to-bed transfers was associated with an increased mortality risk (HR 2.957; CI 1.678–5.211). Also, individuals with severe (HR 0.492; CI 0.290–0.865) and moderate (HR 0.574; CI 0.355–0.927) ADL dependence had a reduced mortality risk when more independent in chair-to-bed transfers. Among people with moderate ADL dependence, this percentage was 48%. Using dependence-independence for chair-to-bed transfer as a screening test for mortality, the test showed high sensitivity (0.91) and specificity (0.83), a positive likelihood ratio of 5.45, and a negative likelihood ratio of 0.11. The area under the ROC curve was 0.814 (CI 0.658–0.970; p = 0.001), with a χ2 = 0.235; p = 0.889, according to the Hosmer–Lemeshow test. The concordance C index was 0.814. According to Nagelkerke’s R2, the model explained 53.1% of the variance in survival. As a screening test, “chair-to-bed transfer” was superior to the Barthel index.ConclusionADL dependence for chair-to-bed transfers is an independent risk factor for mortality for any level of dependency. Therefore, a new classification of the Barthel index is proposed, in which “being dependent or requiring great assistance to perform chair-to-bed transfers” is considered severe dependence, even when the total score obtained via the Barthel Index is ≥40. We propose its use as a screening test in parallel to the Barthel index. The study suggests that the Barthel Index may have limitations in adequately discriminating mortality risk.